Enhancing Communicative Online Language Skills through ICT-Based English Learning Platforms - Zeni Nurhalizah; Yeni Erlita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This study explores the role of Information and Communication Technology (ICT)-based English learning platforms in enhancing Communicative Online Language Skills (COLS). The research investigates how the integration of technology contributes to improving learners’ communicative competence in virtual learning environments. Through a qualitative analysis of previous studies and empirical findings, the study identifies that ICT tools foster interaction, learner engagement, and authentic language use. Platforms such as Moodle, Zoom, and Google Classroom are shown to provide flexible and collaborative spaces where learners can develop confidence and fluency in English communication. Furthermore, the findings highlight that ICT integration encourages learner autonomy and supports a shift from teacher-centered to learner- centered pedagogy. Despite challenges such as limited access and varying digital literacy levels, the overall results emphasize that ICT plays a transformative role in promoting meaningful communication and language proficiency in online settings. The study concludes that well-designed ICT-based learning approaches can effectively prepare learners for global communication in the digital era.